Screening genetic resources of Capsicum peppers in their primary centre of diversity in Bolivia and Peru - Zonneveld, M. van; Ramírez, M.; Williams, D.E.; Petz, M.; Meckelmann, S.; Ávila, T.; Bejarano, C.; Ríos, L.; Pena, K.; Jager, M.; Libreros, D.; Amaya, K.; et al. (Public Library of Science, 2015)
For most crops, like Capsicum, their diversity remains under-researched for traits of interest for food, nutrition and other purposes. A small investment in screening this diversity for a wide range of traits is likely to reveal many traditional varieties with distinguished values. One objective of this study was to demonstrate, with Capsicum as model crop, the application of indicators of phenotypic and geographic diversity as effective criteria for selecting promising genebank accessions for multiple uses from crop centers of diversity. A second objective was to evaluate the expression of biochemical and agromorphological properties of the selected Capsicum accessions in different conditions. Four steps were involved: 1) Develop the necessary diversity by expanding genebank collections in Bolivia and Peru; 2) Establish representative subsets of ~100 accessions for biochemical screening of Capsicum fruits; 3) Select promising accessions for different uses after screening; and 4) Examine how these promising accessions express biochemical and agromorphological properties when grown in different environmental conditions. The Peruvian Capsicum collection now contains 712 accessions encompassing all five domesticated species (C. annuum, C. chinense, C. frutescens, C. baccatum, and C. pubescens). The collection in Bolivia now contains 487 accessions, representing all five domesticates plus four wild taxa (C. baccatum var. baccatum, C. caballeroi, C. cardenasii, and C. eximium). Following the biochemical screening, 44 Bolivian and 39 Peruvian accessions were selected as promising, representing wide variation in levels of antioxidant capacity, capsaicinoids, fat, flavonoids, polyphenols, quercetins, tocopherols, and color. In Peru, 23 promising accessions performed well in different environments, while each of the promising Bolivian accessions only performed well in a certain environment. Differences in Capsicum diversity and local contexts led to distinct outcomes in each country. In Peru, mild landraces with high values in health-related attributes were of interest to entrepreneurs. In Bolivia, wild Capsicum have high commercial demand.